Systematic review and meta-analysis of community pharmacy error rates in the USA: 1993–2015. Issue 4 (2nd October 2018) - Campbell, Patrick J; Patel, Mira; Martin, Jennifer R; Hincapie, Ana L; Axon, David Rhys; Warholak, Terri L; Slack, Marion
Abstract : Importance: While much is known about hospital pharmacy error rates in the USA, comparatively little is known about community pharmacy dispensing error rates. Objective: The aim of this study was to determine the rate of community pharmacy dispensing errors in the USA. Methods: English language, peer-reviewed observational and interventional studies that reported community pharmacy dispensing error rates in the USA from January 1993 to December 2015 were identified in 10 bibliographic databases and topic-relevant grey literature. Studies with a denominator reflecting the total number of prescriptions in the sample were necessary for inclusion in the meta-analysis. A random effects meta-analysis was conducted to estimate an aggregate community pharmacy dispensing error rate. Heterogeneity was assessed using the I 2 statistic prior to analysis. Results: The search yielded a total of 8490 records, of which 11 articles were included in the systematic review. Two articles did not have adequate data components to be included in the meta-analysis. Dispensing error rates ranged from 0.00003% (43/1 420 091) to 55% (55/100). The meta-analysis included 1 461 128 prescriptions. The overall community pharmacy dispensing error rate was estimated to be 0.015 (95% CI 0.014 to 0.018); however, significant heterogeneity was observed across studies (I 2 =99.6). Stratification by study error identification methodology was found to have a significant impact on dispensing error rate (p<0.001). Conclusion and relevance: There are few published articles that describe community pharmacy dispensing error rates in the USA. Thus, there is limited information about the current rate of community pharmacy dispensing errors. A robust investigation is needed to assess dispensing error rates in the USA to assess the nature and magnitude of the problem and establish prevention strategies.